Plant-Microbiome Interactions in Hydrocarbon-Contaminated Soils - Agnello, Ana Carolina (2020)
The use of green remediation technologies (i.e., phytoremediation, bioremediation, mycoremediation) for the restoration of hydrocarbon-contaminated sites is one of the keys for sustainable development. These technologies rely on the joint action of biotic components of the ecosystem, namely, plants, bacteria, and fungi. Despite the fact that previous studies showed that the clean-up of hydrocarbons could be achieved individually by plants or microorganisms, present investigations suggest that the interaction of plants with their surrounding microbiome determines the outcomes of green remediation technologies. This book chapter reviews the state of the art to explain the two-way relationship established between plants and their associated microbiome in hydrocarbon-polluted soils. Special focus is put on stressing the results obtained in recent studies that employ omics approaches.